2022
DOI: 10.1093/cercor/bhac106
|View full text |Cite
|
Sign up to set email alerts
|

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males

Abstract: Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…A number of factors limits our study. First, all our experiments were performed only in male rodents, even though sex differences may play a significant role in behavioural responses to pharmacological challenges (Kalinichenko et al 2021(Kalinichenko et al , 2022. Research showed that the results of many behavioural tests, including FST, EPM, OF, amphetamine-and apomorphine-induced locomotion, varied significantly not only after pharmacological interventions, but also during baseline activity (Simpson et al 2012;Knight et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of factors limits our study. First, all our experiments were performed only in male rodents, even though sex differences may play a significant role in behavioural responses to pharmacological challenges (Kalinichenko et al 2021(Kalinichenko et al , 2022. Research showed that the results of many behavioural tests, including FST, EPM, OF, amphetamine-and apomorphine-induced locomotion, varied significantly not only after pharmacological interventions, but also during baseline activity (Simpson et al 2012;Knight et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour was recorded automatically by the TSE Systems software using infrared sensors. The apparatus measured parameters for each compartment separately (Kalinichenko et al 2021(Kalinichenko et al , 2022.…”
Section: Experiments II Effects Of Aph199 On the Establishment Of Alc...mentioning
confidence: 99%
See 3 more Smart Citations